Thickness effects on the martensite transformations and mechanical properties of nanocrystalline NiTi wires - Baigonakova, Gulsharat A.; Marchenko, Ekaterina S.; Kovaleva, Marina A.; Chudinova, Ekaterina A.; Volinsky, Alex A.; Zhang, Yi (Nanomaterials)
This paper studied the features of the martensitic transformations and mechanical properties of 40, 60, and 90 µm thick NiTi wires with nanocrystalline B2 structures. It was established that the wires were composites and consisted of a TiNi matrix and a TiO2 + TiNi3 surface layer. Structural methods showed that the wire matrix was formed by grains of up to 20 nm in size. The method of measuring the electrical resistivity during cooling and heating revealed a two-stage nature of the martensitic transformation. Cyclic loading–unloading demonstrated that all the samples exhibited superelasticity effects and completely restored their shape when unloaded from a 4–8% relative strain at room temperature. An increase in mechanical characteristics with respect to the wire thickness was experimentally established. This was due to the change in the composition of the TiNi matrix during drawing.